STUDI LABORATORIUM EKSPERIMEN IMBIBISI UNTUK PREDIKSI PENINGKATAN PEROLEHAN MINYAK DI SUMUR X LAPANGAN Y DENGAN INJEKSI NUTRISI - Hadi Amirudin, Nur
The level of oil production in Indonesia has declined. The decline in oil production caused by oil production wells are generally old while oil production from new wells are relatively limited (Indonesia Energy Outlook 2014). Therefore, it is necessary to maximize the production of oil from old wells. One method to increase oil recovery is Enhanced Oil Recovery (EOR). EOR technology which take advantage of the activity of microorganisms known as Microbial Enhanced Oil Recovery (MEOR). Characteristics of oil in the reservoir can be modified using the products produced by microorganisms in the reservoir. This study discusses the influence of MEOR, in this case using nutrients, to the characteristics of the oil and to increase the oil recovery in field Y. This study was conducted with the following stages: 1) Creating artificial sandstone cores to mimic reservoir rocks in field Y, 2) Saturating cores by formation water to fill the pores of the rock with formation water and also with the in-situ bacteria in the formation water, 3) Injecting oil into the cores so that cores are filled with water and oil, as is the case in the reservoir, 4) Producing oil from rocks with injeksi air to know how much oil could be produced from these rocks and how much oil is left, 5) Doing spontaneous imbibition test by using nutrients to see how much oil left from the previous process can be produced, and 6) recording the parameters, that are change of characteristics of the oil after treated by nutrients. From these studies it is known that nutrition affects the oil recovery. Nutrients can increase oil recovery. Nutrients affects the characteristics of oil in field Y, this can be seen from the decrease in viscosity of the oil field Y from 7,2045 cp became 5,193 cp and decrease ini interfacial tension oil and water from 13,6 dyne/cm became 8,15 dyne/cm. Additionally, oil recovery is also increased. Core 25 which is treated by water formation only yield RF = 3.75%, core 23 which is treated by nutrient yield RF = 10%, and core 48 which is treated by nutrient that previously had been grown in-situ bacteria yield the greatest RF, that is 16%.